2019
DOI: 10.1111/are.14002
|View full text |Cite
|
Sign up to set email alerts
|

Microbial communities in sea cucumber (Apostichopus japonicus) culture pond and the effects of environmental factors

Abstract: This study investigated microbial community composition as well as their correlation with environmental factors of Apostichopus japonicus culture ponds in northern China by 16S rRNA gene amplicon sequencing. The results showed that microbiota richness varied consistently with diversity in the pond ecosystem. Microbiota richness and diversity were highest in sediment, followed by gut of A. japonicus and water. The dominant bacterial phylum in the pond ecosystem is Proteobacteria. Gammaproteobacteriaeria and Fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Previous study has confirmed that the composition and diversity of intestinal microbiota of middle-intestine were significantly different from the hind-intestine in the aquatic animal 24 , and the composition of intestinal microbiota in aquaculture animal was related to microbial community composition in sediment 21 , 25 . However, the bacterial composition of different parts of crab intestine and bacterial co-occurrence relationships between crab intestine and sediment remained unknown.…”
Section: Introductionmentioning
confidence: 70%
“…Previous study has confirmed that the composition and diversity of intestinal microbiota of middle-intestine were significantly different from the hind-intestine in the aquatic animal 24 , and the composition of intestinal microbiota in aquaculture animal was related to microbial community composition in sediment 21 , 25 . However, the bacterial composition of different parts of crab intestine and bacterial co-occurrence relationships between crab intestine and sediment remained unknown.…”
Section: Introductionmentioning
confidence: 70%
“…It is a bottom dwelling marine deposit feeder that uses its tentacled mouth to consume the topmost sediment layer [4,5]. The sediment contains plant and animal debris, protozoa, diatoms and a diverse selection of bacteria [6][7][8][9][10]. The sediment also hosts the bacteria V. splendidus [10,11] which has been associated with seasonal epidemics of high mortality among the cultured sea cucumbers [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The sediment contains plant and animal debris, protozoa, diatoms and a diverse selection of bacteria [6][7][8][9][10]. The sediment also hosts the bacteria V. splendidus [10,11] which has been associated with seasonal epidemics of high mortality among the cultured sea cucumbers [12,13]. On the other hand, V. splendidus can also coexist in the gut of healthy sea cucumbers [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The sea cucumber (Apostichopus japonicus) is a bottom dwelling marine deposit feeder that uses its tentacled mouth to consume the topmost sediment layer [4,5]. The sediment contains plant and animal debris, protozoa, diatoms and a diverse selection of bacteria [6][7][8][9][10]. Because the bacteria are abundant and have higher nutritional value than the surrounding sediment, they are considered a direct food source for detrivorous holothurians [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Bottom sediments are also inhabited by the opportunistic, potentially infective bacterium Vibrio splendidus [10,20]. V. splendidus is an efficient decomposer, which allows it to thrive in many environments [21,22].…”
Section: Introductionmentioning
confidence: 99%